MODIFIED ULTRAFILTRATION: ROLE IN ADULT CARDIAC SURGICAL HAEMOSTASIS - Zahoor, Mahrukh; Abbass, Safdar; Khan, Asif Ali; Ahmad, S. Afzal (Journal of Ayub Medical College Abbottabad, 2007)
Background: During cardiac surgery, cardiopulmonary bypass (CPB) leads to haemodilutional anaemia and activation of inflammatory mediators, affecting haemostasis. Modified Ultrafiltration (MUF) is being increasingly favoured for haemoconcentration without blood transfusion and reducing post operative bleeding. Methods: Aim of this study was to record the impact of modified ultrafiltration on haemoconcentration and postoperative bleeding during adult cardiac surgery. This randomized control trial included 100 patients, divided into 2 groups; MUF and control group. Serial blood samples were drawn to evaluate haematological indices. Postoperative chest drainage was recorded for 24 hours. Results were expressed in terms of percentages, means and p value (p<0.05 was taken as significant). Results: Four patients were excluded and 96 patients were analyzed (MUF n=50, control n=46). According to American society of anaesthetist (ASA) classification, MUF group was higher risk group (p=0.02) with longer extracorporeal perfusion time (p<0.001). Haemoconcentration was successfully achieved in MUF group (final haemoglobin=10.7±1.25, haematocrit=33±3.64%, p<0.001) with lower blood loss (MUF=395±153 ml, control=755±435 ml, p<0.001) and transfusion requirement (p<0.001). Re-exploration rate was 4% and 6.5% in MUF and control group respectively (p=0.57). Mortality in both groups was comparable (MUF=4%, control=4.3%, p=0.94). Conclusions: Modified ultrafiltration is a safe procedure which successfully achieves haemoconcentration, lowers blood loss and transfusion requirement after cardiac surgery in adult population. Key words: Modified ultrafiltration, haemoconcentration, haemostasis in cardiac surgery